A single session of hatha yoga improves stress reactivity and recovery after an acute psychological stress task—A counterbalanced, randomized-crossover trial in healthy individuals. (December 2017) - Benvenutti, Mateus J.; Alves, Eduardo da Sliva; Michael, Scott; Ding, Ding; Stamatakis, Emmanuel; Edwards, Kate M.
Highlights: A single session of yoga accelerates blood pressure recovery from acute stress. Cortisol reactivity to acute stress is ameliorated by Yoga. Self-confidence towards a math task is increased by Yoga. Abstract: Objectives: Yoga is promoted as an anti-stress activity, however, little is known about the mechanisms through which it acts. The present study investigated the acute effects of a hatha yoga session, displayed on a video, on the response to and recovery from an acute psychological stressor. Methods: Twenty-four healthy young adults took part in a counterbalanced, randomized-crossover trial, with a yoga and a control condition (watching TV). Participants attended the laboratory in the afternoon on two days and each session comprised a baseline, control or yoga task, stress task and recovery. Blood pressure (BP), heart rate (HR) and salivary cortisol responses were measured. State cognitive- and somatic-anxiety along with self-confidence were assessed before and after the stressor. Results: Although no difference in the BP or HR responses to stress were found between conditions, systolic BP (p = 0.047) and diastolic BP (p = 0.018) recovery from stress were significantly accelerated and salivary cortisol reactivity was significantly lower (p = 0.01) in the yoga condition. A yoga session also increased self-confidence (p = 0.006) in preparation for the task and after completion. Moreover, self-confidence reported after the stress task was considered debilitative towards performance in the control condition, but remained facilitative in the yoga condition. Conclusion: Our results show that a single video-instructed session of hatha yoga was able to improve stress reactivity and recovery from an acute stress task in healthy individuals. These positive preliminary findings encourage further investigation in at-risk populations in which the magnitude of effects may be greater, and support the use of yoga for stress reactivity and recovery.